2002
DOI: 10.1097/00003246-200209000-00006
|View full text |Cite
|
Sign up to set email alerts
|

Effect of continuous lateral rotational therapy on the prevalence of ventilator-associated pneumonia in patients requiring long-term ventilatory care*

Abstract: In patients requiring long-term ventilator care, continuous lateral rotational therapy reduced the prevalence of pneumonia but did not seem to affect mortality or the period of mechanical ventilation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
28
0
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 56 publications
(30 citation statements)
references
References 21 publications
1
28
0
1
Order By: Relevance
“…Nonetheless, a recent survey by the University Hospital Consortium revealed that compliance with the simple and no-cost intervention of elevating the head is woefully low, and a study by Heyland et al revealed that the head of bed is on average elevated to 29°and not 45° (80). Kinetic bed therapy has also led to a reduction in the incidence of VAP (46,48,69,72,97,202,213). However, this is costly and has not been directly compared to head-of-bed elevation, a nocost option.…”
Section: Preventionmentioning
confidence: 99%
“…Nonetheless, a recent survey by the University Hospital Consortium revealed that compliance with the simple and no-cost intervention of elevating the head is woefully low, and a study by Heyland et al revealed that the head of bed is on average elevated to 29°and not 45° (80). Kinetic bed therapy has also led to a reduction in the incidence of VAP (46,48,69,72,97,202,213). However, this is costly and has not been directly compared to head-of-bed elevation, a nocost option.…”
Section: Preventionmentioning
confidence: 99%
“…Physician staffing [20,21] Noninvasive ventilation [22,23] Ventilator associated pneumonia [24-27] Patient-to-nurse ratio [16,[28][29][30][31] SDD [32] Deep venous thrombosis [33][34][35] Mattresses or pressure-relieving beds [9] TISS score by discharge [36] Pulmonary embolism [33][34][35] Daily sedation interruption policy [37] Unplanned extubation [38,39] Decubitus [9] Use of case management approach [40] Continuous lateral rotational therapy [24,41,42] Stress ulcer [43] Computerized physician order entry [44] Interclinical transport [45][46][47] Quality of life [15] Pharmacist participation during daily rounds [16] Red cell concentrate transfusion [48,49] Hospital mortality rate [32,50] Weaning following a protocol [10] Nutrition support [51][52][53][54] Berenholtz et al: Protocol for admission and discharge [11] Glucose regulation [55,…”
Section: Indicator Selectionmentioning
confidence: 99%
“…Passive and active-assisted mobilisation [15,[23][24][25][26][27][28][29] Continuous rotational therapy [30][31][32] Postures [18,[33][34][35][36][37][38][39][40] Active limb exercise [41][42][43] Peripheral muscle training [44,45] Neuromuscular electrical stimulation [46][47][48][49][50][51][52][53][54][55] Respiratory muscle training [56][57][58][59][60] Airway secretions…”
Section: Muscle Weaknessmentioning
confidence: 99%